Environmental education in Tobago’s primary schools: a case study of coral reef education - Armstrong, Hyacinth G. (2005)
Environmental education is a relatively new area on the primary school curriculum of Trinidad and Tobago. Because of the close relationship between human activities and the degradation of the natural environment in Tobago, environmental education will become increasingly important to the preservation and conservation of the island’s fragile natural resources. Current teaching methods rely heavily on text books and utilise a lecture style that does not promote student interaction. Unfortunately, these methods are not very conducive to environmental education. As such, this paper examines a pilot program in which staff from the Buccoo Reef Trust taught students from 15 primary schools about coral reefs using interactive tools and hands-on methods as described in People & Corals: an Education Package for Primary Schools (People & Corals). The pilot program ran over an eight week period with prepared lessons being taught every two weeks and student evaluations taking place once before the first lesson and once after the last lesson. The lessons were supplemented with a field trip to a coral reef ecosystem. Despite several challenges that were faced in the implementation process, the overall outcome of the pilot program was successful. Teachers and students reacted positively to the information that was being shared, thereby reinforcing the effectiveness of using a dynamic, active method of teaching to advance environmental education.